Contact Analysis and Tooth Profile Optimization Design of Rack and Pinion for Rack-rail Trains Based on the Finite-length Line Contact Theory - Lei Huanhuan; Zhao Jiadong; Zhi Yanfeng; Shi Lubing; Zhao Yukai; Yue Zihao (Jixie chuandong)
In order to investigate the influence of the error of center distance between the driving pinion and rack track meshing and the error of axis non-parallelism on the contact stress distribution during the curved driving of rack-rail trains, an analytical model of rack and pinion contact stresses is established based on the finite-length line contact theory by considering the two kinds of errors comprehensively. Comparison with the finite element simulation of rack and pinion contact under error conditions shows that the established model has good computational accuracy. Based on the model, the contact stress response under different error levels and the combined two types of errors are investigated, the effects of the two types of errors on the contact stress distribution are revealed, and countermeasures are proposed accordingly. The results show that the proposed contact stress analysis model can accurately respond to the contact condition of the rack and pinion under the combined effect of the meshing center distance error and the axial non-parallelism error. The contact stress level increases with the increase of the meshing center distance error. The degree of axial non-uniformity of contact stresses increases with the increase of axis non-parallelism error. The meshing center distance error enhances the axial contact stress inhomogeneity caused by the axial non-parallelism error, and the axial non-parallelism error has a slight inhibitory effect on the effect of the meshing center distance error. The intrinsic mechanism of the meshing center distance error is the reduction of the load carrying area at the same load level, and the intrinsic mechanism of the axial non-parallelism error is the greater deformation produced by the rack and pinion taking the lead in contact on the inside of the curve. Root gouging of the pinion eliminates the effect of axial non-parallelism error, and helix modification of the pinion reduces the effect of axial non-parallelism error.